1H- and 13C-NMR Analysis of a Series of 1,2-Diaryl-1H-4,5-dihydroimidazoles - Isabel A. Perillo; Alejandra Salerno (Molecules, 2005)
An analysis of the 1H- and 13C-NMR spectra of a series of 1,2-diaryl-1H-4,5-dihydroimidazoles and comparisons with 4,5-dihydroimidazoles having differentsubstitution patterns are presented. The influence of different 1-aryl and 2-aryl groupsubstituents on spectroscopic parameters of the heterocyclic ring and on the contributionsof possible mesomeric structures in the system was determined. Spectroscopic featuresare coherent with the presence of two conjugated systems (Ar1-N and Ar2-C=N) whichcompete with the delocalization characteristics of the amidine system.